1961
DOI: 10.1210/endo-69-4-844
|View full text |Cite
|
Sign up to set email alerts
|

OVARIAN ASCORBIC ACID AS AN ENDOGENOUS AND EXOGENOUS ASSAY FOR CYCLIC PROESTROUS LH RELEASE1

Abstract: Cyclic proestrous LH release was investigated by endogenous and exogenous assay in rats exposed to light from 5:00 A.M. to 7:00 P.M. daily. Pituitaries were removed from proestrous rats at 10:00-11:00 A.M. and 4:00-5:00 P.M., injected into immature, primed recipient rats and tested for ovarian ascorbic acid depleting ability (exogenous assay). "Morning" pituitaries were significantly more potent than "afternoon" pituitaries, confirming the finding of drug and hypophysectomy studies that LH is released from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1967
1967
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Decreases in the pituitary content of FSH during cyclic oestrus or immediately preceding it have been reported in the ewe (Santalucito, Clegg & Cole, 1960;Robertson & Hutchinson, 1962) and sow (Day, Anderson, Hazel & Melampy, 1959;Parlow et al 1964) and decreases in LH have been observed in the rat (Mills & Schwartz, 1961;Gorski & Barraclough, 1962;Schwartz & Bartosik, 1962), ewe (Santalucito et al 1960;Robertson & Hutchinson, 1962) and sow . These decreases were considered to represent release of the hormones to produce ovulation and the follicular growth immediately preceding it.…”
Section: Resultsmentioning
confidence: 87%
“…Decreases in the pituitary content of FSH during cyclic oestrus or immediately preceding it have been reported in the ewe (Santalucito, Clegg & Cole, 1960;Robertson & Hutchinson, 1962) and sow (Day, Anderson, Hazel & Melampy, 1959;Parlow et al 1964) and decreases in LH have been observed in the rat (Mills & Schwartz, 1961;Gorski & Barraclough, 1962;Schwartz & Bartosik, 1962), ewe (Santalucito et al 1960;Robertson & Hutchinson, 1962) and sow . These decreases were considered to represent release of the hormones to produce ovulation and the follicular growth immediately preceding it.…”
Section: Resultsmentioning
confidence: 87%
“…The small number of such mice available prevented the testing of this hypothesis. Both the time of lh release and the time of ovulation in the mice with a longer cycle (and at least the time of ovulation in the mice with a shorter cycle) are later than that found in the rat with a shorter cycle; lh is released between 14.00 and 16.00 hours at pro-oestrus and the rat ovulâtes close to 02.00 hours at oestrus (Everett, 1961;Mills & Schwartz, 1961;Schwartz & Bartosik, 1962;Schwartz & Caldarelli, 1965). An exact comparison of mice exhibiting 5-day cycles with rats exhibiting this cycle length, awaits further investigation in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat exhibiting either 4-or 5-day oestrous cycles, the surge of lh responsible for ovulation is released from the anterior pituitary after 14.00 hours on the day of pro-oestrus (lights on from 05.00 to 19.00 hours) (Mills & Schwartz, 1961;Schwartz & Bartosik, 1962;Schwartz & Caldarelli, 1965). Untreated 4-day cyclic rats housed under conditions of 14 hr light and 10 hr darkness (L14:D10; 24.00 hours = midpoint of the dark period) ovulate at about 02.00 hours on the morning of oestrus (Everett, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…The data from the PMSG-primed females compare favourably with the pituitary lh information on the adult cycling rat (Mills & Schwartz, 1961;Schwartz & Bartosik, 1962) where pituitary lh decreased during the critical period, but lowest lh values were seen on the morning of oestrus. However, no pituitary change was seen between 14.00 and 19.00 hours in PMSG-ovulated 27-day-old females, but a significant fsh decrease occurred (Rennels & O'Steen, 1967 (Ramirez & Sawyer, 1965a) have shown an increase in the lh-rf in prooestrus, continuing for some time after the critical period, and followed by a decrease which is maintained into the morning of oestrus.…”
Section: Introductionmentioning
confidence: 60%
“…Progesterone administration on the day before pro-oestrus in 5-day cycling adult female rats causes ovulating hormone release 24 hr earlier than normal (Everett & Sawyer, 1949b (Ramirez & McCann, 1964;Schwartz & Calderelli, 1965). Phénobarbital blocked the lh increase in the afternoon of pro-oestrus (Schwartz & Calderelli, 1965 (Cole, 1936;Strauss & Meyer, 1962 (Mills & Schwartz, 1961;Schwartz & Bartosik, 1962;Rennels & O'Steen, 1967) have been shown to decrease during the critical period and both exogenous lh and fsh can cause ovulation (Zarrow, Caldwell, Hafez & Pincus, 1958;Zarrow & Gallo, 1966 0/9 0/9 0/9 0/9 0/9 0/9 0/9 0/9 0/9 0/9 0/9 9/9 9/9 9/9 9/9Î 9/9t 9/9Î 9/9Î 0/9 0/9 0/9 0/9 0/9 9/9 9/9 9/9 9/9Í 0/12 11/11 12/12 9/9 10/llt 10/llt 13/13Î 12/12J (5/9)t (6/8) (4/9) (4/9) (4/9) (4/9) (7/9) (3/9) (4/9) (3/9) (0/9) (0/9) (0/9) (0/9) (0/9) (0/9) (0/9) (0/9) (7/9) (4/9) (3/9) (3/8) (1/9) (0/9) (0/9) (0/9) (0/9) (3/12) (1/ ) (1/12) (1/9) (1/11) (1/11) (0 (7/9) (9/9) (9/9) (9/9) (8/9) (8/9) (8/9) (8/9) (9/9) (8/9) (6/9) (0/9) (1/9) (1/9) (2/9) (4/9) (1/9) (3/9) (9/9) (9/9) (7/9) (9/9) (2/9) (0/9) (1/9) (0/9) (1/9) (8/12) (4/11) (7/12) (8/9) (7/11) (10/11) (6/13) (7 (Bogdanove, 1964). Therefore, in the 16.30 PB rat oh synthesis occurs.…”
Section: Introductionmentioning
confidence: 99%